2016
DOI: 10.1213/ane.0000000000001328
|View full text |Cite
|
Sign up to set email alerts
|

No Pain Labor & Delivery: A Global Health Initiative’s Impact on Clinical Outcomes in China

Abstract: The availability of labor analgesia is highly variable in the People's Republic of China. There are widespread misconceptions, by both parturients and health care providers, that labor epidural analgesia is harmful to mother and baby. Meanwhile, China has one of the highest cesarean delivery rates in the world, exceeding 50%. The goal of the nongovernmental No Pain Labor & Delivery (NPLD) is to facilitate sustainable increases in vaginal delivery rates by increasing access to safe neuraxial labor analgesia, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…[22][23][24] Data from India and China reveal rates of labour epidural analgesia of 11% and 1%, respectively, with the rate in China increasing to 50% following a major intervention over 10 years. [14,15] An audit at Tygerberg Hospital, Cape Town, SA, showed an epidural rate of 2.2%, which is in keeping with the findings of this audit. [16] This increased to 5.2% after the establishment of a dedicated epidural service.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[22][23][24] Data from India and China reveal rates of labour epidural analgesia of 11% and 1%, respectively, with the rate in China increasing to 50% following a major intervention over 10 years. [14,15] An audit at Tygerberg Hospital, Cape Town, SA, showed an epidural rate of 2.2%, which is in keeping with the findings of this audit. [16] This increased to 5.2% after the establishment of a dedicated epidural service.…”
Section: Discussionsupporting
confidence: 84%
“…Data regarding the proportion of women receiving labour epidural analgesia in developing countries are limited, but it is assumed to be much lower than in developed countries. Hu et al [14] reported a labour epidural rate of less than 1% in China in 2007. This was increased to 50% in some hospitals following the No Pain Labor & Delivery initiative.…”
mentioning
confidence: 99%
“…One report from Georgia cited lack of governmental funding for supplies, lack of familiarity of anesthesia staff with current techniques and evidence-based guidelines, and limited availability of appropriate local anesthetics as possible reasons (10). Another survey of RA use from the Czech Republic cited patient fear over the safety of RA and lack of acceptance by obstetric providers (9), similar to a report of an ongoing collaboration in China between Chinese and American anesthesia providers (11). …”
Section: Introductionmentioning
confidence: 66%
“…Obstetrician preference may have a larger effect than that of the anesthesiologist in the choice of RA versus GA and efforts directed at obstetrician education to adequately answer patient questions concerning RA may be as important as those directed toward patients in increasing patient acceptance (10). An added benefit is that it may also overcome obstetrician reluctance to RA use (9, 1113, 15). Ninidze et al (10), Kopic et al (12) Olufolabi et al (13), and Schnittger (15) all cited obstetrician reluctance to operating on an awake patient as a potential barrier to use of RA for CD.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the present study could not rule out the potential effects of anesthesia, which has been demonstrated to increase the abundance of Ruminococcus in horse fecal microbiota, 48 h after anesthesia ( Schoster et al, 2016 ). Firstly, this limitation arose due to the inability to recruit women who had elected to receive epidural analgesia during labor, owing to widespread belief (among both pregnant women and health care providers in China) that epidural analgesia is harmful to the mother and baby ( Hu et al, 2016 ). Secondly, catheterization was refused, even among women who elected to receive epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%